HUBUNGAN UKURAN LINGKAR PINGGANG DENGAN FREKUENSI PERNAPASAN PADA WANITA USIA SUBUR DI KELURAHAN RENGAS PULAU KECAMATAN MEDAN MARELAN KOTA MEDAN - RAMYAS PRAREDA SUBHI; IRFAN DARFIKA LUBIS (LP2MTBM MAKARIOZ, 2023)
The waist is the part of the human body that is located on a horizontal line between the costal arch and the iliac crest. The waist is in the pelvic region. Waist circumference is often used as an alternative marker of abdominal fat mass. Normal respiratory rate in adults is 14-20 breaths per minute. Breathing less than 12 times per minute is called bradypnea, while breathing more than 20 times per minute is called tachypnea. This research is a descriptive analytic study with a cross sectional approach. The research subjects were 100 women of childbearing age living in Rengas Pulau Village, Medan Marelan Subdistrict, Medan City who met the inclusion criteria. Waist circumference with respiratory rate has a significant value with a correlation coefficient of 0.838 (p=0.000). Based on the results of this study, it can be concluded that there is a significant relationship between waist circumference and respiratory rate in the overall sample with a very strong correlation. Further research is needed by examming measurement in other anthropometric fields such as body mass index, hip circumference, abdominal circumference, upper arm circumference, and chest circumference which have a correlation with respiratory frequency.